DOI: 10.26686/wgtn.16992799
|View full text |Cite
|
Sign up to set email alerts
|

Group Mentoring of New Graduate Midwives: Emerging Professional Capacity: A Naturalistic Inquiry

Abstract: <p>This research explores an innovative group mentoring model developed at the request of four newly graduated midwives who were mentored as a group by four experienced midwives. Since virtually all research on mentoring, both internationally and in New Zealand assumes that mentoring is a one-to-one activity, this study aimed to describe how this group mentoring model operated and explore whether it was successful in supporting new midwives to gain confidence. A naturalistic study design was used with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 100 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…Previous studies from Aotearoa have reported on the efficacy and benefits of midwifery mentoring from the perspective of mentee and new graduate midwives (Jackson, 2020;Kensington, 2006;Lennox, 2011;Lennox et al, 2008;Pairman et al, 2016;Stewart & Wootton, 2005). Likewise, international literature on mentoring relationships in midwifery has focused on the experiences of mentees and student midwives, or programme efficacy (Bradford et al, 2022;Cummins et al, 2017;Ryan et al, 2010;Wissemann et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies from Aotearoa have reported on the efficacy and benefits of midwifery mentoring from the perspective of mentee and new graduate midwives (Jackson, 2020;Kensington, 2006;Lennox, 2011;Lennox et al, 2008;Pairman et al, 2016;Stewart & Wootton, 2005). Likewise, international literature on mentoring relationships in midwifery has focused on the experiences of mentees and student midwives, or programme efficacy (Bradford et al, 2022;Cummins et al, 2017;Ryan et al, 2010;Wissemann et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of mutual trust, respect and a non-hierarchical and safe environment to facilitate successful mentoring relationships has been identified in the wider literature on midwifery mentoring (Bradford et al, 2022;Cummins et al, 2017;Jefford et al, 2021;Kensington, 2006;Ryan et al, 2010). This also reflects how mentee midwives in Aotearoa describe their experience of the mentoring relationship as providing a safe yet challenging space (Lennox, 2011) and a safe environment to reflect on practice (Stewart & Wootton, 2005), which enable mentees to feel safe, comfortable and secure (Kensington, 2006).…”
Section: The Role Of the Mentormentioning
confidence: 95%
See 2 more Smart Citations